A Criticism on the Field of Political Studies of the Islamic Revolution: The Convergence of the Four Methodological Domains - Zahed Ghafari Hashjin; Mohammad Aghaei (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
As an event, the Islamic Revolution of Iran is seen as intertwined series of various factors and as a flow, it is considered as a nominal figure of innumerable events. Obviously, extensive studies are needed to study the broad dimensions of such a phenomenon. The present article aims at understanding the aspects of the political studies of the Islamic Revolution in the context of the interdisciplinary doctoral study and which is being implemented. In this perspective, the main question of the present study is how has the field of political studies of the Islamic Revolution been able to gain a comprehensive understanding of the political epistemological domain of the Islamic Revolution? The findings of the research based on qualitative method analysis and documentary studies, the data collection of which was based on notetaking tools show that the placement of the concept of Islamic Revolution at the intersection of four methodological fields of political thought of Islamic Revolution leaders, political sociology of Islamic Republic, futures study of Islamic revolution , and the reflection of the Islamic Revolution has succeeded in achieving a proper understanding of the political aspect of the Islamic Revolution as a coherent model by applying four different and, of course, cross-sectional methods.